David's secret demons messiah, murderer, traitor, king - Halpern, Baruch (Grand Rapids, MI Eerdmans, 2001)
Includes bibliographical references and index.
Keywords: Bible. O.T. Samuel -- criticism, interpretation, etc; David, King of Israel